Integrin Crosstalk and Its Effect on the Biological Functions of the Trabecular Meshwork/Schlemm’s Canal - Faralli, Jennifer A.; Filla, Mark S.; Peters, Donna M. (Frontiers in Cell and Developmental Biology, 2022)
Integrins are a family of heterodimeric receptors composed of an α- and β- subunit that mediate cell-adhesion to a number of extracellular matrix (ECM) proteins in the Trabecular Meshwork/Schlemm’s canal (TM/SC) of the human eye. Upon binding an ECM ligand, integrins transmit signals that activate a number of signaling pathways responsible for regulating actin-mediated processes (phagocytosis, cell contractility and fibronectin fibrillogenesis) which play an important role in regulating intraocular pressure (IOP) and may be involved in glaucoma. An important function of integrin-mediated signaling events is that the activity of one integrin can affect the activity of other integrins in the same cell. This creates a crosstalk that allows TM/SC cells to respond to changes in the ECM presumably induced by the mechanical forces on the TM/SC, aging and disease. In this review, we plan to discuss how integrin crosstalk influences the function of the human TM/SC pathway. In particular, we will discuss how different crosstalk pathways mediated by either the αvβ3 and α4β1 integrins can play opposing roles in the TM when active and therefore act as on/off switches to modulate the cytoskeleton-mediated processes that regulate the outflow of aqueous humor through the TM/SC.